Characteristic of ichthyofauna of Tentek River (Eurasian Journal of Ecology, 2016)
During our survey of the Tentek River the species of four families: Balitoridae, Cyprinidae, Percidae and Eleotridae were observed. Two-thirds of them are aboriginal species. The largest diversity of fish communities are found in the lower section of the river. Results of the our study confirmed the Nemacheilus sewerzowi living in the Alakol-Sasykkol Lake System. Now Pseudorasbora parva became common species for Tentek River. Despite the presence of alien species and predators, most native species are relatively favorable conditions for their existence, even in the lower section of the Tentek River, where a invasive fish species are most active.
Keywords: native species; rare species; alien species; ichthyofauna; communities.